Credit Markets and Narrow Banking - Ronnie Phillips (Levy Economics Institute of Bard College, 1992)
Maurice Allais's view that the credit created by fractional reserve banking is equivalent to counterfeiting has led him to recommend the separation of the depository and lending functions of banks. This proposal has recently been reintroduced by James Tobin and others under the term "narrow banking." Proponents cite the potential for enhanced safety of the payments mechanism and the elimination of costs associated with the preses system of Federal deposit insurance. This plan resembles the "100% reserves" and "100% money" proposals submitted by Irving Fisher, Henry Simons, and others in the 1930s. The essence of banking today is that banks borrow short and lend long, while Allais's proposal would require the reverse: borrow long and lend short. Among Allais's objections to the fractional reserve system are the creation and destruction of money by private banks, the impossibility of control over the credit system, and the lack of efficient control of the aggregate money supply. The fundamental principles guiding reform are that (i) the creation of money should be the business of only the state, and (ii) no money should be created outside the monetary base, so that no one would be entitled to the benefits that attach to the creation of bank money. A corollary to this proposal is that the availability of credit is limited to just what the private sector is willing to lend on an equity basis. Phillips addresses the common shortcomings of previous reform proposals (e.g. Peel's Act of 1844 and 100% reserve plans of the 1930s), which failed to recognize the existence of substitutes to banknotes and demand deposits. The lingering question is how to "construct financial institutions which do not impede the development of the economy, yet are flexible enough to allow for technological innovation and market discipline." Narrow banking is a response (though not a panacea) to this dilemma, which clarifies the fundamental principles involved and "allows a way out of the Federal deposit insurance mess."
Keywords: 330